Overview of Dry and Wet Food Storage Using the FIFO and FEFO Methods at the Nutrition Installation of Datu Beru Regional Hospital, Central Aceh - Ayunda, Hanif Muchdatul; Irtantri, Syahriza; Safrida, Safrida; Febriansyah, Muhammad Irfan (Journal of Nutrition Science, 2024)
Hospitals as food providers for patients and staff require standardized food storage systems to maintain quality and safety. This study aims to evaluate the compliance of dry and wet food storage using FIFO (First In First Out) and FEFO (First Expired First Out) methods at the Nutrition Installation of Datu Beru Hospital, Aceh Tengah, based on the Pelayanan Gizi Rumah Sakit Kementerian Kesehatan (PGRS KEMENKES) 2013 guidelines. Quantitative descriptive research with a cross-sectional design was conducted through direct observation and assessment sheets using the Guttman Scale on 5 storage staff. Results showed dry food storage scored 9 out of 12 (meeting requirements), but inconsistencies were found in unscheduled warehouse opening, daily room cleaning (twice a day instead of twice a week), and absence of insecticide spraying. Wet food storage scored 7 out of 7 (meeting requirements), though improvements in storage time management are needed. The conclusion states that FIFO and FEFO methods have been implemented with proper stock recording, but improvements in warehouse schedules, cleaning frequency, and pest control are required. Further research should explore causes of non-compliance and develop localized strategies for enhancing adherence.